RESEARCH ON DYNAMIC CHARACTERISTICS DURING MILLING OF THIN-WALLED PARTS BASED ON MAGNETO RHEOLOGICAL DAMPING FIXTURE (MT) - JIANG XiaoHui; YANG Ning; HE ShiRong; LIU Xiao (Jixie qiangdu)
Additive thin-walled parts have the characteristics of complex features and weak rigidity, which are prone to processing chatter vibration during the subsequent local feature milling and finishing. Therefore, this paper designed an electromagnetic magnetorheological damping fixture to semi-actively suppress processing vibration and improve processing quality. By simplifying the thin-walled part of the additive into a rectangular thin plate, considering the magneto-rheological fluid（MRF） excitation solidification damping characteristics, using the mode superposition method, the dynamic response model of the milling of the thin-walled part under the change of the magnetic induction intensity was obtained, and the fixture-workpiece system milling. The maximum error between the predicted value of dynamic response and the measured value is 21.4%. The feasibility and effectiveness of the method were verified through modal hammer percussion experiments and milling experiments, and the matching relationship between milling force, process parameters and magnetic induction intensity was fitted. Finally, the processing quality test of the typical samples was carried out. The processing flatness and roughness are increased by 80.0% and 80.3% respectively. The electromagnetic magneto-rheological damping fixture can effectively suppress the milling chatter, improve the processing stability of thin-walled parts, and improve the surface processing of the workpiece quality.